2015
DOI: 10.1016/j.marpolbul.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Levels of arsenic, cadmium, lead and mercury in the branchial plate and muscle tissue of mobulid rays

Abstract: Mobulid rays are targeted in fisheries for their branchial plates, for use in Chinese medicine. Branchial plate and muscle tissue from Mobula japanica were collected from fish markets in Sri Lanka, and muscle tissue biopsies from Manta alfredi in Australia. These were analysed for arsenic, cadmium, lead and mercury and compared to maximum levels (MLs) set by Food Standards Australia and New Zealand (FSANZ), European Commission (EC) and Codex Alimentarius Commission. The estimated intake for a vulnerable human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In order to evaluate whether ingestion leads to bioaccumulation in tissues, researchers should measure phthalate, heavy metal, and POP levels in mobulid tissue biopsies from wild populations and samples collected from fisheries. Previous studies found elevated levels of some heavy metals in mobulid tissues (Essumang, 2009(Essumang, , 2010Ooi et al, 2015), but low levels of POPs (Germanov et al, in prep; Fernando, unpublished). Phthalates and/or POPs have been recorded in tissue samples of baleen whales, basking sharks and whale sharks in areas with high levels of microplastic pollution (Fossi et al, 2014(Fossi et al, , 2016(Fossi et al, , 2017, indicating that filter feeding organisms are likely bioaccumulating these pollutants as a result of plastic ingestion.…”
Section: Identifying Trophic Interactions With Pollutantsmentioning
confidence: 83%
“…In order to evaluate whether ingestion leads to bioaccumulation in tissues, researchers should measure phthalate, heavy metal, and POP levels in mobulid tissue biopsies from wild populations and samples collected from fisheries. Previous studies found elevated levels of some heavy metals in mobulid tissues (Essumang, 2009(Essumang, , 2010Ooi et al, 2015), but low levels of POPs (Germanov et al, in prep; Fernando, unpublished). Phthalates and/or POPs have been recorded in tissue samples of baleen whales, basking sharks and whale sharks in areas with high levels of microplastic pollution (Fossi et al, 2014(Fossi et al, , 2016(Fossi et al, , 2017, indicating that filter feeding organisms are likely bioaccumulating these pollutants as a result of plastic ingestion.…”
Section: Identifying Trophic Interactions With Pollutantsmentioning
confidence: 83%
“…species (e.g., foul-hooking, vessel strikes, entanglement, climate change, pollution, tourism) through research, monitoring, modeling, and management (NOAA 2020) Pate & Marshall (2020). and our SDMs suggest that manta rays are frequently associated with nearshore habitats; as such, they are at elevated risk for exposure to a variety of contaminants and pollutants, including brevetoxins, heavy metals, polychlorinated biphenyls, and plastics(Essumang 2010;Ooi et al 2015). Many of these toxins can bioaccumulate over decades in long-lived lter feeders, leading to a disruption of biological processes (e.g., endocrine disruption), and potentially altering reproductive tness(Germanov et al 2019).…”
mentioning
confidence: 82%
“…Ironically, consumption of unregulated animal products from unknown sources carries a number of potential health risks from heavy metal accumulation, toxic chemicals used in processing, and zoonotic transmission of infectious diseases (Still, ; Clarke et al ., ; Alves et al ., ). Mobulid gill plates and tissues tested have been found to contain potentially unsafe levels of heavy metals, including arsenic, cadmium, and mercury (Essumuang, ; Whitcraft et al ., ; Oi et al ., ), with some gill plate samples tested exceeding the Pharmacopoeia of China recommended limit for arsenic by as much as 20 times (Li et al ., ; Whitcraft et al ., ).…”
Section: Discussionmentioning
confidence: 99%